Humidity interaction of lichens under astrobiological aspects: the impact of UVC exposure on their water retention properties. Issue 3 (July 2015) - Jänchen, J.; Meeßen, J.; Herzog, T.H.; Feist, M.; de la Torre, R.; deVera, J.-P.P.
Abstract We quantitatively studied the hydration and dehydration behaviour of the three astrobiological model lichens Xanthoria elegans, Buellia frigida and Circinaria gyrosa by thermoanalysis and gravimetric isotherm measurements under close-to-Martian environmental conditions in terms of low temperature and low pressure. Additionally, the impact of UVC exposure on the isolated symbionts of B. frigida and X. elegans was studied by thermoanalysis and mass spectrometry as well as by gravimetric isotherm measurements. The thermal analysis revealed whewellite as a component of C. gyrosa which was not found in B. frigida and X. elegans. Neither the water retention nor the thermal behaviour of symbionts changed when irradiated with UVC under dry conditions. On the other hand, UVC irradiation of the wet mycobiont of B. frigida had a distinct impact on the hydration/dehydration ability which was not observed for the mycobiont of X. elegans. Possibly the melanin of B. frigida's mycobiont, that is not present in X. elegans, or a specifically damaged acetamido group of the chitin of B. frigida may be the sources of additional UVC-induced sorption sites for water associated with the UVC exposure.